1998
DOI: 10.2116/analsci.14.79
|View full text |Cite
|
Sign up to set email alerts
|

Response Characteristics of Anion-Selective Polymer Membrane Electrodes Based on Gallium(III), Indium(III) and Thallium(III) Porphyrins

Abstract: With the evolution of ion-selective ionophore-based liquid/polymer membrane electrodes (ISEs) over the past 25 years, many cations of physiological and industrial significance can be measured effectively by direct potentiometry. However, there is a noticeable lack of analogous electrodes for many common anions. 1 Although commercial electrodes based on anionexchangers such as quaternary ammonium salts can be analytically useful, their selectivity patterns are always correlated solely with anion lipophilicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 40 publications
5
68
0
Order By: Relevance
“…Similarly, thus far, relatively few useful fluoride-selective polymeric membrane electrodes have been reported [8][9][10][11][12][13][14][15]. Most suffer from practical problems such as high level of interference by lipophilic anions [11,12,15], super-nernstian response slopes, sluggish and not fully reversible response properties [8,9,10,14] and short use lifetimes of the electrodes [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, thus far, relatively few useful fluoride-selective polymeric membrane electrodes have been reported [8][9][10][11][12][13][14][15]. Most suffer from practical problems such as high level of interference by lipophilic anions [11,12,15], super-nernstian response slopes, sluggish and not fully reversible response properties [8,9,10,14] and short use lifetimes of the electrodes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most suffer from practical problems such as high level of interference by lipophilic anions [11,12,15], super-nernstian response slopes, sluggish and not fully reversible response properties [8,9,10,14] and short use lifetimes of the electrodes [14]. Recent research has suggested that membranes formulated with Al(III) octaethylporhyrin (Al [OEP]) and Al(III) tetraphenylporphyrin (Al[TPP]) [14] exhibit very high potentiometric selectivity towards fluoride anions, and this has led also to the design of highly selective optical fluoride sensors with sub-micromolar fluoride ion detection limit [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…19 Recently it was found that polymer membranes doped with Ga(III) and Zr(IV) porphyrins exhibit an enhanced potentiometric selectivity for fluoride due to the ability of these species to interact selectively with fluoride ion via a preferred axial ligation reaction. [20][21][22][23][24] Further, it appears that the Ga(III) and Zr(IV) porphyrins may be useful for preparing bulk-optode sensing films for fluoride without the need for addition of a suitable pH indicator, owing to the ability of fluoride ion binding to the respective metal ion centers to alter the equilibrium between monomeric porphyrins and hydroxide ion bridged dimeric porphyrins within the polymeric film. 20-23 The dimer and monomeric species have different Soret band λ max for absorption.…”
Section: Introductionmentioning
confidence: 99%
“…PPHR complexes with transition metal ions are very stable and are often used to construct structures in supramolecular chemistry, taking advantage of the Lewis acidity of the coordinated metal [16]. Several metalloporphyrins have been employed as electroactive components in the membrane of potentiometric sensors, and their response to anions has been interpreted by a dissociation ion-exchange mechanism or metal-ligand interaction mechanism [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%